The Effect of Ginger in Relieving Nasal Congestion in Influenza Sufferers in Negeri Agung Village, Selagai Lingga, Central Lampung in 2024 - Setia Puspa Agung; Fajar Yudha; Fitri Anita (Journal of Education Technology Information Social Sciences and Health, 2024)
Influenza is an infectious disease caused by the microorganism of the influenza virus. Therefore, an easy and inexpensive measure is needed to overcome nasal congestion in influenza sufferers, namely the administration of ginger. The purpose of this study is to determine the effect of ginger in relieving nasal congestion in influenza patients in Negeri Agung Village, Selagai Lingga District, Lampung Tengah Regency in 2024. This type of research is quantitative with a two-group design research design. The total population was 177 influenza patients in Negeri Agung village in June and the sample amounted to 44 respondents. The instruments in this study are in the form of observation sheets and data analysis using an independent statistical test t-test. The results of the study obtained that the average time of nasal congestion in the group of influenza patients who were given ginger was 7.86 minutes and the group that was not given ginger was 22 minutes. There was an effect of ginger in relieving nasal congestion in influenza patients in Negeri Agung Village, Selagai Lingga, Lampung Tengah with a p-value of 0.000.